(untitled) (Sumatera Medical Journal, 2025)
Background: Anemia in pregnancy can have a negative impact on pregnant women and the fetus in the womb. Objective: This study aimed to determine the prevalence of anemia in pregnant women at the Medan Tuntungan Health Center in 2023. Methods: This research was conducted at the Medan Tuntungan Health Center with data for 2023. The research design was a cross-sectional, quantitative descriptive design. The research 8sample was pregnant women who carried out Antenatal Care (ANC) examinations at the Medan Tuntungan Health Center. Results: A total of 107 pregnant women met the inclusion criteria. The majority of pregnancies were in the second trimester (46,7%), primigravida (40,2%), good nutrition (88.8%), below middle school education (53,3%), and non-working (73,8%). The prevalence of anemia for pregnant women at the Medan Tuntungan Health Center in 2023 was 27,1% with an average Hb level of pregnant women experiencing anemia of 9,48 g/dL. Conclusion: The prevalence of anemia in pregnant women was 27,1%.